(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In the article, the lexical features of cosmonomes in Alisher Navoi’s epic "Layli and Majnun" are highlighted. The onomastic scope of the epic, i.e., the issues of using proper nouns, was analyzed.